(untitled) (Journal of actual problems of jurisprudence, 2019)
In the article are analyzed the actual problems of planning and organizing crime’s counteraction system, is defi ned the whole complex of principal proposition, oriented on solution of basic problems crime counteraction, is distinguished with basic subsection of crime’s counteraction system, which were system of counter crime, system of detection crime, system of criminal identifi cation, system of impact crime, system of impact on society.